DEVELOPED VILLAGES, DEVELOPED UMKM: A SERVICE AND SOCIALISATION PROGRAMME FOR LOCAL ECONOMIC GROWTH - Melyana R Pugu; Muhammad Syafri; Iwan Kusnadi (Adiba Aisha Amira, 2024)
The ‘Desa Maju, UMKM Berkembang’ programme is a community service initiative that aims to improve local economic growth through the development of Micro, Small, and Medium Enterprises (MSMEs) in villages. In the context of sustainable economic development, MSMEs play a vital role as drivers of the grassroots economy. However, MSMEs in rural areas often face various challenges, including limited access to capital, markets, technology, and modern management knowledge. Thus, the ‘Desa Maju, MSMEs Berkembang’ programme has demonstrated the effectiveness of a holistic approach in the development of rural MSMEs. The programme has not only succeeded in improving the economic capacity of individuals and groups, but has also contributed to strengthening the overall economic structure of the village.